2018
DOI: 10.1073/pnas.1715378115
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of cotranscriptional alternative splicing underlies CHARGE syndrome

Abstract: CHARGE syndrome-which stands for coloboma of the eye, heart defects, atresia of choanae, retardation of growth/development, genital abnormalities, and ear anomalies-is a severe developmental disorder with wide phenotypic variability, caused mainly by mutations in (chromodomain helicase DNA-binding protein 7), known to encode a chromatin remodeler. The genetic lesions responsible for mutation-negative cases are unknown, at least in part because the pathogenic mechanisms underlying CHARGE syndrome remain poorly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
108
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(130 citation statements)
references
References 86 publications
22
108
0
Order By: Relevance
“…Downstream Semaphorin and Robo pathways are critical to neural crest development and migration and may be involved in CHD7 ‐negative CHARGE syndrome (S R Lalani et al, ; Liu, Guo, et al, ; Schulz et al, ; Ufartes et al, ). Additionally, there is also evidence that the disruption of Fam172a, which interacts with CHD7 and Argo2, can affect alternative splicing in neural crest cells and lead to a CHARGE phenotype (Bélanger et al, ), with neural crest cells being particularly sensitive to disruption of splicing machinery (Bérubé‐Simard & Pilon, ). However, not all aspects of CHARGE can be related to the role of CHD7 on neural crest development.…”
Section: Patterns Of Congenital Heart Disease In Chargementioning
confidence: 99%
“…Downstream Semaphorin and Robo pathways are critical to neural crest development and migration and may be involved in CHD7 ‐negative CHARGE syndrome (S R Lalani et al, ; Liu, Guo, et al, ; Schulz et al, ; Ufartes et al, ). Additionally, there is also evidence that the disruption of Fam172a, which interacts with CHD7 and Argo2, can affect alternative splicing in neural crest cells and lead to a CHARGE phenotype (Bélanger et al, ), with neural crest cells being particularly sensitive to disruption of splicing machinery (Bérubé‐Simard & Pilon, ). However, not all aspects of CHARGE can be related to the role of CHD7 on neural crest development.…”
Section: Patterns Of Congenital Heart Disease In Chargementioning
confidence: 99%
“…In the Toupee mouse model of CHARGE syndrome [22], mutagenic transgene sequences are inserted in the last intron of Fam172a, generating a hypomorphic allele that negatively affects almost every aspect of NCC ontology (migration, proliferation, survival and differentiation). Yet, we found that Fam172a expression is not restricted to this cell lineage, being instead almost ubiquitously expressed in embryonic day (e)8.5 to e12.5 embryos.…”
Section: Fam172a: a New Intriguing Regulator Of Cotranscriptional Altmentioning
confidence: 99%
“…In a sustained and concerted effort to identify neurocristopathy-associated genes [18][19][20][21], we recently generated a mouse model for CHD7 mutation-negative CHARGE syndrome, by random insertional mutagenesis of the poorly characterized gene Fam172a [22]. We found that Fam172a codes for a new Ago2-binding protein that seems to be essential for stabilizing proteinprotein interactions at the chromatin-spliceosome interface.…”
Section: Introductionmentioning
confidence: 99%
“…Both these molecular processes lead to protein synthesis, which is crucial for neural crest cell survival. Image modeled after Hallgrimsson et al , Belanger et al , and Calo et al …”
Section: Developmental Processes Linking Spliceosomopathies and Ribosmentioning
confidence: 99%
“…Both these molecular processes lead to protein synthesis, which is crucial for neural crest cell survival. Image modeled after Hallgrimsson et al 2014, Belanger et al 2018, and Calo et al 2018 of NCCs appear to be particularly sensitive to perturbation, which may imply a high demand for protein synthesis in these cells. However, rescue of NCC survival by down-regulation of p53 in Tcofdeficient mice occurs independently of ribosome biogenesis (Jones et al, 2008).…”
Section: Protein Synthesismentioning
confidence: 99%